Cost study application of the guidebook on integrated community energy systems: indirect economic and energy impacts - United States. Department of Energy. (Argonne National Laboratory, 1978)
An ICES is being considered for a community located in a small New England city. (MCW) It is part of the city's newer development. It is a commercial park of offices, shopping center, bank, hospital, and hotel. The ICES for this community is designed to meet all heating, cooling, steam, and hot water needs. Electricity from the cogeneration unit is to be sold to the local utility, and electricity for the community will be purchased as at present. However, future electrical demand will be reduced, since absorption chillers, which will be powered by heat recovered from the central ICES unit, will partially replace electric air conditioners. In addition, hot-water heating from ICES will, in some cases, lower electrical use. Thus, the ICES involves substitution of energy forms as well as modification of fuel requirements. Examination of the integrated system, in comparison with existing energy systems, includes both indirect economic impacts (employment and fiscal effects on the city) and indirect energy impacts. The indirect economic analysis proceeds from an initial description of conditions that determine employment and fiscal results through specific estimates of employment and then revenues and costs to municipal government and finally to an evaluation of ICES's worth to the city. The indirect energy analysis compares energy resource requirements of the ICES with those for gas, oil, and electric systems now serving the community. (MCW)